Moisture absorption behavior and thermal properties of sucrose replacer mixture containing inulin or polydextrose - Wong, Keat Yi; Thoo, Yin Yin; Tan, Chin Ping; Siow, Lee Fong (Elsevier BV, 2022)
The increasing consumer awareness of healthier food choices with low calories and high fiber content has driven the development of sucrose-free dark compound chocolate enriched with dietary fiber. Therefore, this study aimed to determine the effect of adding dietary fiber-low digestible carbohydrate (LDC) polymer on the moisture sorption behavior and thermal properties of a sucrose replacer mixture. Duo-trio and acceptance tests were also conducted to identify the relative sweetness of sucrose replacer compared to that of sucrose. Among these samples, erythritol-polydextrose mixture and tagatose-inulin mixture have similar sweetness levels as sucrose at P ≥ 0.05. Most sucrose replacer mixtures were well-accepted by panelists, except the trehalose-polydextrose mixture. Moisture content, hygroscopicity, and thermal properties of the sucrose replacer mixture were also studied. The result showed that all sucrose replacer mixtures had significantly (P<0.05) higher moisture content than sucrose. The addition of LDC polymer altered the moisture content, hygroscopicity, and melting temperature of the samples due to its amorphous nature and large molecular structure. Considering the average relative humidity in tropical countries was reported at 65% RH, the sucrose replacer mixtures containing erythritol, mannitol, or tagatose could replace sucrose in dark compound chocolate of their low moisture content and hygroscopicity at aw of 0.65.